Do Behavioral Biases Vary across Individuals? Evidence from Individual Level 401(k) Data - Agnew, Julie R. (Journal of Financial and Quantitative Analysis, 2006)
Abstract This paper investigates whether some individuals are prone to behavioral biases in their 401(k) investments. Using demographic data and allocation information for over 73,000 employees, I examine two allocation biases and a participation bias. The findings suggest that higher salaried employees tend to make significantly better choices. Participants who earn $100, 000 hold 12. 7% less in company stock, are 3% less likely to follow the framing 1/ n heuristic, and are 37.7% more likely to participate than those earning $46, 000. Women make better choices in two of the three cases and I find evidence of mental accounting.